Alternative splicing of DENND1A, a PCOS candidate gene, generates variant 2. (15th October 2016) - Tee, Meng Kian; Speek, Mart; Legeza, Balázs; Modi, Bhavi; Teves, Maria Eugenia; McAllister, Janette M.; Strauss, Jerome F.; Miller, Walter L.
Abstract: Polycystic ovary syndrome (PCOS) is a common endocrinopathy characterized by hyperandrogenism and metabolic disorders. The excess androgens may be of both ovarian and adrenal origin. PCOS has a strong genetic component, and genome-wide association studies have identified several candidate genes, notably DENND1A, which encodes connecdenn 1, involved in trafficking of endosomes. DENND1A encodes two principal variants, V1 (1009 amino acids) and V2 (559 amino acids). The androgen-producing ovarian theca cells of PCOS women over-express V2. Knockdown of V2 in these cells reduces androgen production, and overexpression of V2 in normal theca cells confers upon them a PCOS phenotype of increased androgen synthesis. We report that human adrenal NCI-H295A cells express V1 and V2 mRNA and that the V2 isoform is produced by exonization of sequences in intron 20, which generates a unique exon 20A, encoding the C-terminus of V2. As in human theca cells from normal women, forced expression of V2 in NCI-H295A cells resulted in increased abundance of CYP17A1 and CYP11A1 mRNAs. We also found genetic variation in the intronic region 330 bp upstream from exon 20A, which could have the potential to drive the selective expression of V2. There was no clear association with these variants with PCOS when we analyzed genomc DNA from normal women and women with PCOS. Using minigene expression vectors in NCI-H295A cells, this variable region did not consistently favor splicing of the V2 transcript. These findings suggest increased V2 expression in PCOS theca cells is not the result of genomic sequence variation in intron 20. Highlights: Polycystic ovary syndrome (PCOS) includes hyperandrogenism and metabolic dysfunctions. Genome-wide association studies have identified DENND1A as a candidate gene for PCOS. PCOS theca cells overexpress DENND1A variant 2 (V2; 559 AA), but not V1 (1009 AA). V2 arises by exonization within intron 20 generating a unique exon 20A Overexpression of V2 in human adrenal cells increases CYP11A1 and CYP17A1 mRNAs. Genetic variation 330 bp upstream of exon 20A is not associated with expression of V2.